IBM IN DESA TUA TUNU INDAH THROUGH MARKETING STRATEGY BASED ON INFORMATION TECHNOLOGY - Vebtasvili Vebtasvili; Desy Yuliana Dalimunthe (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
This activity is conducted on Small and Medium Micro Enterprise (UMKM)